EVALUATION OF ANTI-HYPERGLYCEMIC ACTIVITIES OF PHLORIDZIN IN DIABETIC MICE - Liang, ZhenHong; Liu, XiaoHong; Gong, ShuMei (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The aim of the study was to investigate the hypoglycemic effects of Phloridzin. Methods and Materials: High fat diet induced diabetic KKAy mice were administered with phloridzin at an oral dose (60 mg/kg/day, ig.) for 10 weeks. A range of parameters, including blood glucose and lipid, serum insulin, glucose tolerance, were tested to evaluate its anti-hyperglycemic effects. Results: Phloridzin decreased water-intake, body weight, FBG, FINS, HOME-IR, Serum leptin, and CRP levels, increased serum adiponectin level in diabetic mice. Phloridzin also improved the oral glucose tolerance test (OGTT) to a certain degree. In addition, phloridzin decreased liver index, and epididymal, perirenal white adipose tissue indexs, increased pancreas index in diabetic mice. At last, phloridzin increased hepatic GK activity and hepatic glycogen level, decreased hepatic PEPCK, G-6-Pase activities in diabetic mice. Conclusions: Phloridzin possessed anti-hyperglycemic activities.